A microsimulation model for the development and progression of chronic obstructive pulmonary disease. Issue 12 (December 2015) - Tan, Emma; Boessen, Ruud; Fishwick, David; Klein Entink, Rinke; Meijster, Tim; Pronk, Anjoeka; van Duuren-Stuurman, Birgit; Warren, Nick
Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic lung disease that is thought to affect over one million people in Great Britain. The main factor contributing to the development of COPD is tobacco smoke. This paper presents a microsimulation model for the development of COPD, incorporating population dynamics and trends in smoking. The model simulates a population longitudinally throughout their lifetimes, providing projections of future COPD prevalence and evaluation of the effects of changes in risk factor prevalence such as smoking. Sensitivity analysis provides information on the most influential model parameters. The model-predicted prevalence of COPD in 2040 was 17% in males over the age of 35 years (13% amongst non-smokers and 22% amongst smokers), and a modest decline over the next 25 years due to recent trends in smoking rates. The simulation model provides us with valuable information on current and future trends in COPD in Great Britain. It was developed primarily to enable easy extension to evaluate the effects of occupational and environmental exposures on lung function and the prevalence of COPD and to allow evaluation of interventions, such as introducing health surveillance or policy changes. As longitudinal studies for investigating COPD are difficult due to the lengthy follow-up time required and the potentially large number of drop-outs, we anticipate that the model will provide a valuable tool for health impact assessment. An extended model for occupational exposures is under development and will be presented in a subsequent paper. Highlights: We present a stochastic microsimulation model for the development and progression of COPD, incorporating trends in smoking. Model-predicted prevalence of COPD in GB was 17% in males aged 35+ years (13% in non-smokers and 22% in smokers). The model is anticipated to provide a valuable tool for health impact assessment. The model enables easy extension to evaluate the effects of occupational and environmental exposures.